2020
DOI: 10.1177/1073274820936287
|View full text |Cite
|
Sign up to set email alerts
|

High Biologically Effective Dose Radiotherapy for Brain Metastases May Improve Survival and Decrease Risk for Local Relapse Among Patients With Small-Cell Lung Cancer: A Propensity-Matching Analysis

Abstract: To evaluate whether high biologically effective dose (BED) radiotherapy improves local control and survival outcomes for patients with brain metastases (BMs) from small-cell lung cancer (SCLC) and to determine possible prognostic factors. From January 1998 to June 2018, 250 patients with BM from SCLC were retrospectively analyzed. The Cutoff Finder program was used to classify patients by BED. Overall survival (OS) and BM progression-free survival (BM-PFS) were analyzed using the Kaplan-Meier method a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Single SRS was conducted in 189 patients while FSRS (2–3 fx) in 167 patients. The median biologically effective dose (BED) of radiation was 41.6 Gy (IQR 41.6–50.4) for the α/β value of 10 ( 16 ). In the overall cohort, the median OS was 17.7 months (95% CI 15.5–19.9).…”
Section: Resultsmentioning
confidence: 99%
“…Single SRS was conducted in 189 patients while FSRS (2–3 fx) in 167 patients. The median biologically effective dose (BED) of radiation was 41.6 Gy (IQR 41.6–50.4) for the α/β value of 10 ( 16 ). In the overall cohort, the median OS was 17.7 months (95% CI 15.5–19.9).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, RT is an irreplaceable treatment for BM [3,4,22,23] . However, an increased radiation dose, particularly to vascular endothelial cells and glial cells, is associated with increased toxicity and reduced tolerance to treatment [24] .…”
Section: Discussionmentioning
confidence: 99%
“…BM is a signi cant health problem whose incidence is increasing, and the median survival time is only 1-2 months without treatment [1,19−21] . Numerous studies have indicated that increasing the dose of RT signi cantly improves the local control of BM, and some patients have achieved long-term survival [22,23] .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the injected activity or number of cycles could be tailored to reach the best TCP, whilst lowering the NTCP as in WBRT. For instance, the TCP model of WBRT is based on a biologically effective dose of about 40 Gy ( 38 ). Usually, a fractionation of 10 times 3 Gy is delivered to the patient after a CT planning scan.…”
Section: Radioimmunotherapy Of Early Bmmentioning
confidence: 99%